The link between breastfeeding profile and contraceptive use and barriers to breastfeeding: messages from a breastfeeding support center on the need for further strategies to improve breastfeeding - Koçakoğlu, Şenay (Frontiers in Pediatrics, 2025)
Background and objectivesThe aim of this study is to evaluate the barriers to breastfeeding in a region with high fertility rates from the perspective of a breastfeeding support center (BSC). The broader aim of the study is to inform policymakers about the need to expand breastfeeding support centers and integrate family planning services (FPCs) into these centers.MethodsData from 2,714 postpartum mothers from the tertiary hospital affiliated BSC in Şanlıurfa, Türkiye (2020–2024), were analyzed. Group comparisons were made based on contraceptive use, delivery mode, maternal educational level, and seasonal work status.ResultsContraceptive users had significantly better breastfeeding outcomes: The average duration of breastfeeding for previous first-born infants was significantly longer among contraceptive users (16.68 months, 95% CI: 15.10–18.26) compared to non-users (11.16 months, 95% CI: 10.02–12.30), p < .001.The mean duration of breastfeeding for all surviving children was also longer among contraceptive users (18.82 months, 95% CI: 17.20–20.44) vs. non-users (13.05 months, 95% CI: 11.78 to 14.32), p < .001.ConclusionsThe findings of this study underscore the need to support breastfeeding, increase women's knowledge and awareness of contraceptive methods, and to enhance access to integrated family planning and breastfeeding counseling services, including via mobile and outreach modalities. Integrating FPCs into breastfeeding support centers (BSCs), particularly in regions with high fertility rates, low educational attainment, and where sociocultural norms strongly influence attitudes, can be a rational and effective strategy to improve maternal and child health by positively impacting breastfeeding outcomes.